The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1029/95jd02195
|View full text |Cite
|
Sign up to set email alerts
|

Pinatubo volcanic aerosol layer decay observed at Ahmedabad (23°N), India, using neodymium:yttrium/aluminium/garnet backscatter lidar

Abstract: Pinatubo volcanic aerosol layer is studied with a neodymium:yttrium/aluminium/garnet (Nd:YAG) (532 nm) backscatter lidar system at the Physical Research Laboratory, Ahmedabad (23°N, 72.5°E), India, from April 1992 to May 1994. The results obtained on the integrated mass densities and aerosol backscatter from 17 to 30 km show a 1/e‐folding time of 9 months, for the Pinatubo aerosol layer to decay. Calculations show that if the layer decays at the same rate, then it may take about 4.5 years for the stratosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Parameswaran et al (1991) reported an agreement that was satisfactory between lidar and SAGE II with large variability in tropospheric extinction. Aerosol extinctions between lidar and SAGE II compared well in the 17-30 km altitude region after the Mt Pinatubo eruption (Jayaraman et al, 1995). The lidar profiles were found to match fairly well with the SAGE II profiles (version 6.20) when the spatial separation between the instruments was in the order of a few hundreds of kilometres .…”
Section: P Kulkarni and S Ramachandran: Comparison Of Aerosol Extinsupporting
confidence: 53%
See 1 more Smart Citation
“…Parameswaran et al (1991) reported an agreement that was satisfactory between lidar and SAGE II with large variability in tropospheric extinction. Aerosol extinctions between lidar and SAGE II compared well in the 17-30 km altitude region after the Mt Pinatubo eruption (Jayaraman et al, 1995). The lidar profiles were found to match fairly well with the SAGE II profiles (version 6.20) when the spatial separation between the instruments was in the order of a few hundreds of kilometres .…”
Section: P Kulkarni and S Ramachandran: Comparison Of Aerosol Extinsupporting
confidence: 53%
“…(1) at Trivandrum (Parameswaran et al, 1991) during volcanically quiescent conditions, (2) at Ahmedabad after the Mt Pinatubo volcanic eruption (Jayaraman et al, 1995) and (3) at Gadanki . It is to be noted that, in general, the comparisons between lidar and SAGE II focussed on instrument capabilities and were restricted to a limited number of days in the case of (1) and (2).…”
Section: P Kulkarni and S Ramachandran: Comparison Of Aerosol Extinmentioning
confidence: 99%
“…One of them was done under stratospheric aerosol background conditions using data from Trivandrum, India (8.6°N, 77°E) for the first months of 1987 [ Parameswaran et al , 1991]. The other comparison was conducted right after the Mount Pinatubo eruption at Ahmedabad (23°N, 72.5°E) in April 1992 [ Jayaraman et al , 1995].…”
Section: Previous Stratosphere Aerosol and Gas Experiments (Sage) Ii‐lmentioning
confidence: 99%
“…Pinatubo whenever SAGE II had an occultation pass around the respective lidar location. Most of the earlier inter-comparisons between the aerosol extinction profiles obtained from SAGE-II and lidar (Lu et al, 1997;Russell and McCormick, 1989;Rizi et al, 2000;Yue et al, 1995;Jayaraman et al, 1995) were carried out over the mid and high latitudes when the lower stratosphere was volcanically disturbed. Only very few such comparisons exist over the tropics under volcanically quiescent conditions.…”
Section: Introductionmentioning
confidence: 99%